Xanthomas in A Warehouse Worker: A Case Report - Harahap, Ummi Chairani; Mulyantini, Astri; Soemarko, Dewi S (The Indonesian Journal of Community and Occupational Medicine, 2023)
Background: Xanthomas are visible external lump that appears on the body. Xanthomas are not tumors, instead, they are collections of foam cells that develop within the skin’s connective tissue, tendons and layers beneath the skin. These formations are significant indicators of disorders in lipid metabolism and are frequently seen in individuals with hypercholesterolemia. This case report describes the case of a male patient who worked in a warehouse with xanthomas and analyzes the relationship between his disease and work.Case Presentation: A 38-year-old man presented at a referral hospital in August 2023 with multiple yellowish elevated masses over the palm of the hands, sole and over the dorsum of the foot. The size of the masses varied between 0.5×0.5×0.5 cm (over the palm of the hands and sole), 1,5x1,5x0,5 cm and 2x1,5x1 cm(over dorsum of the foot) (Figure 1). The patient is accustomed to consuming fatty foods, coffee and alcohol. The patient presented with an elevated level of cholesterol and triglycerides. The patient had symptoms of discomfort and pain,which were due to the large size of the masses.The patient worked in a warehouse and encountered numerous potential hazards. Upon further examination, the patient was diagnosed with xanthomas. Excisional biopsy were performed to remove the massive xanthomas from the palm, sole and dorsum of the foot.Discussion: The process of confirming an occupational illness necessitates following a seven-step method, which considers factors such as clinical diagnosis, individual, and other exposures outside of work. However, in this instance, no work-related, personal, or external environmental elements linked to xanthomas were identified.Conclusion: There is no substantial evidence that occupational exposures as a warehouse worker cause or exacerbate the patient’s diagnosis of xanthomas. Very high cholesterol and triglycerides remain the main contributing factors to the diagnosis.